ANALYSIS OF THE PSYCHOLOGICAL IMPACT OF MODERN INFORMATION TECHNOLOGIES ON THE EDUCATION OF THE YOUNG GENERATION (Scientific journal of the Fergana State University, 2024)
This article examines the psychological impact of modern information technologies on the education of the younger generation. Integrating theoretical perspectives and empirical research, it identifies the positive and negative impacts of digital technologies on students' cognitive, emotional and social development. Research examines how technologies such as the Internet, social media, and educational software affect learning, attention span, and social interactions. It also addresses issues caused by digital distraction, cyberbullying and the digital divide. The article comprehensively analyzes the complex relationship between modern information technology and education through a multi-method approach including literature review, surveys and observational studies. The results highlight the need for balanced and judicious integration of technology into educational environments to maximize benefits while mitigating negative impacts. Practical recommendations are offered to educators, parents, and policymakers to enhance the positive impact of technology on the educational experiences of young students.